Design and Test of a Magneto-Rheological Mount Applied to Start/Stop Mode of Vehicle Powertrains - DENG Zhaoxue (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
In order to overcome the disadvantage of vehicle ride comfort caused by large vibration and torque excitation of vehicle engine in start/stop mode, a flow mode magneto-rheological (MR) mount is designed for low frequency working conditions. Based on the analysis on the influence of exciting current on the viscosity of the MR fluid (MRF) and the relationship between the fluid resistance effect and the flow rate in the damping channel, the magnetic circuit and the damping performance of the MR mount model are analyzed. According to the mathematical model of the MR mount damping force, the multi-objective optimization function of the magnetic circuit is established. The co-simulation optimal platform is developed by using the Isight and ANSYS software. The non-dominated sorting genetic algorithm II (NSGA-II) is used to optimize magnetic circuit design. The dynamic performance test of the MR mount monomer and the vibration isolation performance test of the whole vehicle in start/stop mode are conducted respectively. The results show that the controllable damping force of the optimized MR mount increases by 111.71% and the restoring force increases by 21.99% compared with those before. When the vehicle is in start/stop mode and the excitation current is 1.0A, the peak vibration acceleration of the passive side (the side connected to the body) with the optimized MR mount decreases by 33.3% compared with that before. Besides, the peak vibration acceleration of driver’s seat rail decreases by 21.6%, which significantly improves the ride comfort of the vehicle.